BIOMINERALIZATION AND GLOBAL CHANGES: BRACHIOPOD SHELLS AS ARCHIVES OF THE END PERMIAN EVENTS - C. Garbelli (Università degli Studi di Milano, 2015)
The Permian has been the theatre of major global changes in the Earth’s geodynamics, climate, seawater and atmosphere geochemistry, and thus it represents an interesting case study to understand the response of organisms to environmental changes, a topic which is of increasing interest to the scientific community, who has to face the current global change. In fact, in the Permian the biotic response was dramatic, culminating at the end of the period with the greatest mass extinction of the Phanerozoic. Noteworthy, the end Permian mass extinction coincided with one of the largest known continental eruptions, the Siberian trap basalts, that are considered to have generated more than 100,000 Gt of CO2 as well as CH4, leading to ocean acidification and global warming. Brachiopods, which are low buffered organisms with a heavily calcified shell, can be the perfect candidates to record the trends related to changes in seawater chemistry during this critical interval. The aim of this research is thus to study the biomineralization of brachiopod shells to unravel the patterns of biotic changes caused by the extreme Late Permian events. To reach this goal, I organized my research in three different phases, starting to investigate the main differences in the shell fabric of the brachiopod groups ruling the benthic communities in the Late Permian, that are the classes Rhynchonellata and Strophomenata (phase 1); then comparing the stratigraphic distribution of brachiopod genera during the Late Permian in a paleogeographic perspective (phase 2); finally, analyzing in great details, both qualitatively and quantitatively, the shell fabric of several taxa from Tethyan Permian-Triassic Boundary (PTB) successions, to unravel the biomineralization activity at generic level(phase 3). To develop this research I investigated brachiopods belonging to different paleogeographic localities in the Tethyan realm. The specimens were in part collected by myself during field activity, in part already available from the collections of ...